2008
DOI: 10.1371/journal.pbio.0060287
|View full text |Cite
|
Sign up to set email alerts
|

Kin Discrimination Increases with Genetic Distance in a Social Amoeba

Abstract: In the social amoeba Dictyostelium discoideum, thousands of cells aggregate upon starvation to form a multicellular fruiting body, and approximately 20% of them die to form a stalk that benefits the others. The aggregative nature of multicellular development makes the cells vulnerable to exploitation by cheaters, and the potential for cheating is indeed high. Cells might avoid being victimized if they can discriminate among individuals and avoid those that are genetically different. We tested how widely social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
180
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(191 citation statements)
references
References 36 publications
9
180
1
1
Order By: Relevance
“…During the evolution of multicellularity, a degree of unrelatedness-and therefore conflict-had to be overcome, perhaps by recognition or via some other mechanism [30][31][32][33]. We show that a sufficient degree of structured growth may be sufficient to achieve this, despite the mobility of amoebae that tends to mix cells.…”
Section: Discussionmentioning
confidence: 87%
“…During the evolution of multicellularity, a degree of unrelatedness-and therefore conflict-had to be overcome, perhaps by recognition or via some other mechanism [30][31][32][33]. We show that a sufficient degree of structured growth may be sufficient to achieve this, despite the mobility of amoebae that tends to mix cells.…”
Section: Discussionmentioning
confidence: 87%
“…A couple of studies found some evidence for sorting, particularly between clones collected far apart (58) or, in another study, particularly between clones found close together (59). Neither approached the levels of sorting found in another species, Dictylostelium purpureum (60).…”
Section: Control Of Cheatingmentioning
confidence: 99%
“…However, dissolution and death of multicellular individuals occurs when cooperation breaks down, cancer being a prime example (4). There are multiple mechanisms to help ensure cooperation of component cells in most extant multicellular species (5)(6)(7)(8), but the origin and the maintenance of multicellularity are two distinct evolutionary problems. Component cells in a nascent multicellular organism would appear to have frequent opportunities to pursue noncooperative reproductive strategies at a cost to the reproduction of the multicellular individual.…”
mentioning
confidence: 99%